Effects of the SUMO Ligase BCA2 on Metabolic Activity, Cell Proliferation, Cell Migration, Cell Cycle, and the Regulation of NF-κB and IRF1 in Different Breast Epithelial Cellular Contexts - Shi, Yuhang; Castro-Gonzalez, Sergio; Chen, Yuexuan; Serra-Moreno, Ruth (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer-associated gene 2 (BCA2) is an E3 ubiquitin and SUMO ligase with antiviral properties against HIV. Specifically, BCA2 (i) enhances the restriction imposed by BST2/Tetherin, impeding viral release; (ii) promotes the ubiquitination and degradation of the HIV protein Gag, limiting virion production; (iii) down-regulates NF-kB, which is necessary for HIV RNA synthesis; and (iv) activates the innate transcription factor IRF1. Due to its antiviral properties, ectopic expression of BCA2 in infected cells represents a promising therapeutic approach against HIV infection. However, BCA2 up-regulation is often observed in breast tumors. To date, the studies about BCA2 and cancer development are controversial, stating both pro- and anti-oncogenic roles. Here, we investigated the impact of BCA2 on cellular metabolic activity, cell proliferation, cell migration and cell cycle progression. In addition, we also examined the ability of BCA2 to regulate NF-kB and IRF1 in transformed and non-tumor breast epithelial environments. Despite the fact that BCA2 promotes the transition from G1 to S phase of the cell cycle, it did not increase cell proliferation, migration nor metabolic activity. As expected, BCA2 maintains its enzymatic function at inhibiting NF-kB in different breast cancer cell lines. However, the effect of BCA2 on IRF1 differs depending on the cellular context. Specifically, BCA2 activates IRF1 in ER+ breast cell lines while it inhibits this transcription factor in ER- breast cancer cells. We hypothesize that the distinct actions of BCA2 over IRF1 may explain, at least in part, the different proposed roles for BCA2 in these cancers.